Clinician adherence to the clinical practice guideline: Acute otitis externa. (15th November 2019) - Mildenhall, Nicholas; Honeybrook, Adam; Risoli, Thomas; Peskoe, Sarah B.; Kim, Amie; Kaylie, David
Abstract : Objectives/Hypothesis: Over 10 years have passed since the Clinical Practice Guideline: Acute Otitis Externa (CPG‐AOE) was first published, and it has been several years since its update. We sought to assess clinicians' adherence as well as referral patterns. Study Design: Survey. Methods: A 23‐question survey was distributed to regional primary care clinicians evaluating demographic data, perception of the clinical practice guideline (CPG), adherence, and details of specialist referral. Statistical analysis was performed to compare adherence and referral patterns using the Fisher exact test or the χ 2 test. Results: One hundred seventeen clinicians completed the survey. Fifteen respondents (12.8%) had reviewed the CPG. The recommendations with the least reported adherence were pain management (39.1%) and accounting for prior radiotherapy as a modifying factor (43.0%). The recommendations of prescribing ototopical therapy and avoiding systemic antimicrobials in uncomplicated acute otitis externa had adherence of 94.0% and 83.8%, respectively. When analyzed by provider type (e.g., resident, nurse practitioner/physician assistant), there were no significant differences in adherence. No significant differences in adherence were observed based on previous review of the CPG. When reporting frequency of specialist referral, the majority of respondents selected rarely (53.9%). The most favored reason for referral was symptoms >4 weeks (86.3%). Conclusions: Of the providers who responded, very few had reviewed the CPG‐AOE. Despite the added emphasis on pain management in the CPG update, this recommendation had the lowest adherence. Rates of adherence were similar across provider types and did not differ significantly if the CPG was reviewed. Efforts at improved provider education should be considered to increase adherence to the CPG. Level of Evidence: NA Laryngoscope, 130:1565–1571, 2020